2023
DOI: 10.1186/s12957-023-03068-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in patients with thymoma who underwent surgery

Abstract: Purpose Thymoma is the most common primary tumor in the anterior mediastinum. The prognostic factors of patients with thymoma still need to be clarified. In this study, we aimed to investigate the prognostic factors of patients with thymoma who received radical resection and establish the nomogram to predict the prognosis of these patients. Materials and methods Patients who underwent radical resection for thymoma with complete follow-up data betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Existing knowledge indicates the association of neutrophils and their markers with a worse prognosis in patients with different types of cancer [42]. To illustrate, the study by Yiang et al identified an elevated level of neutrophils as an independent predictor of the OS after a radical thymoma surgery [43]. The first insight into the mechanism linking the impact of neutrophils to tumorigenesis refers to the influence of reactive oxygen species (ROS) released by leukocytes on DNA damage in the pathogenesis of lung cancer [44].…”
Section: Discussionmentioning
confidence: 99%
“…Existing knowledge indicates the association of neutrophils and their markers with a worse prognosis in patients with different types of cancer [42]. To illustrate, the study by Yiang et al identified an elevated level of neutrophils as an independent predictor of the OS after a radical thymoma surgery [43]. The first insight into the mechanism linking the impact of neutrophils to tumorigenesis refers to the influence of reactive oxygen species (ROS) released by leukocytes on DNA damage in the pathogenesis of lung cancer [44].…”
Section: Discussionmentioning
confidence: 99%